GRAYU: graph-based database integrating Ayurvedic formulations, medicinal plants, phytochemicals and diseases - Joshi, Sarthak; Pathak, Aditi; Regati, Dheemanth Reddy; Menon, Revathy; Ajith, Deepthi S.; Sheshadri, Aditya; Viswanathan, Neerja; Ray, Poulomi; Koul, Vimarishi; Panda, Pratishruti; Bhambore, Shriya Anand; Verma, Shailya; et al. (Frontiers in Pharmacology, 2026)
IntroductionThe translation of India's extensive traditional knowledge on indigenous medicinal plants into modern therapeutic solutions is contingent upon a systematic framework. While traditional Indian medicine offers a rich source of therapeutic leads, this knowledge is often not structured for modern computational analysis, creating a barrier to systematic drug discovery.MethodsTo this end, we present GRAYU, a curated and comprehensive online database that integrates data across multiple categories, connecting 1,039 traditional formulations to 12,743 indigenous plants, 129,542 phytochemicals, and 13,480 indicated diseases.ResultsGRAYU provides insights into 1,370,257 plant-phytochemical, 116,531 plant-disease, 2,389 plant-formulation, and 4,087 formulation-disease associations. We show potential applications on phytochemical analogs, sustainable plant substitution, and disease-network analysis, highlighting the potential of integrative graphs to decode shared molecular signatures and therapeutic networks across traditional Ayurvedic formulations.DiscussionGRAYU represents a user-friendly resource for researchers to investigate complex bio-associations and formulate novel therapeutic hypotheses, with insights from traditional Indian medicine. GRAYU organises reported associations and computational relationships and can hint at mechanistic causality or biological activity; however, all outputs require contextual interpretation and further experimental validation. The database is available at https://caps.ncbs.res.in/GRAYU/.